PENERAPAN HUKUM TERHADAP TINDAK PIDANA PENGGELAPAN MOBIL DI KOTA PAREPARE - Muh Fadli Faisal Rasyid (Jurnal Delik ADPERTISI, 2023)
This study aims to determine the application of the law resulting from the crime of car embezzlement in the city of Parepare and to find out the judge's considerations regarding the crime of car embezzlement in the city of Parepare in decision No.158/Pid.Sus/2021/PN.Pare. The type of research used in this research is normative legal research. The source of the legal material used in this research is primary legal material which consists of laws and regulations, official records such as academic texts and minutes of meetings for the formation of laws and regulations, and judges' decisions at both the District Court and Supreme Court levels. and secondary legal materials are legal materials that provide an explanation of primary legal materials in the form of all legal publications that are not official documents. Publications on law include text books and scientific writings related to the object of research. The results of the study can be concluded that the application of material law occurred in the parepare district court decision with Number 158/Pid.Sus/2021/PN.Pare. According to the author is correct. The Public Prosecutor used the first indictment of Article 35 of the Republic of Indonesia Law Number 42 of 1999 concerning Fiduciary Guarantees Jo. Article 55 paragraph (1) 1st of the Criminal Code, and the second indictment of article 36 of the Republic of Indonesia Law Number 42 of 1999 concerning Fiduciary Guarantees Jo. Article 55 paragraph (1) 1st of the Criminal Code, among the elements charged by the Public Prosecutor which is considered legally and convincingly proven is Article 372 of the Criminal Code and also legal considerations by the judge in deciding the decision in Decision Number 158/Pid.Sus/ 2021/PN. Pare. According to the author, it is in accordance with the applicable legal regulations as described by the previous author, namely based on at least two valid pieces of evidence, where in the case that the author examined, the evidence used by the judge was witness testimony and the defendant's statement which was appropriate. Then consider criminal responsibility, in this case the Panel of Judges based on the facts at trial considered that the defendant was aware of the consequences. The perpetrator in carrying out his actions was in a healthy and capable condition to consider his actions. There is an element against the law and there is no reason for criminal abolition.